2010
DOI: 10.2460/ajvr.71.7.809
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 30- and 25-diopter intraocular lens implants in equine eyes after surgical extraction of the lens

Abstract: Insertion of 30-D (enucleated globes) and 25-D IOL implants (adult horses) resulted in overcorrection of refractive error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 11 publications
3
45
0
2
Order By: Relevance
“…Na literatura estrangeira, no entanto, aparece como um procedimento já bem estabelecido em cães (Gaiddon et al, 1997;Gilger et al, 1998;Kecová e Necas, 2004;McMullen et al, 2010), todavia sem conclusões bem definidas sobre como calcular o poder dióptrico corretamente e sem dados objetivos sobre a real vantagem da utilização das lentes intraoculares. Para isso, são necessários mais estudos com implantação de LIOs para obtenção de maior número de dados pós-operatórios de animais, possibilitando a análise da previsibilidade das diversas fórmulas humanas disponíveis, o que pode ser facilitado pelo uso de modelos experimentais com o coelho.…”
Section: Resultsunclassified
“…Na literatura estrangeira, no entanto, aparece como um procedimento já bem estabelecido em cães (Gaiddon et al, 1997;Gilger et al, 1998;Kecová e Necas, 2004;McMullen et al, 2010), todavia sem conclusões bem definidas sobre como calcular o poder dióptrico corretamente e sem dados objetivos sobre a real vantagem da utilização das lentes intraoculares. Para isso, são necessários mais estudos com implantação de LIOs para obtenção de maior número de dados pós-operatórios de animais, possibilitando a análise da previsibilidade das diversas fórmulas humanas disponíveis, o que pode ser facilitado pelo uso de modelos experimentais com o coelho.…”
Section: Resultsunclassified
“…From an optical standpoint, the aphakic eye should be quite far‐sighted or hyperopic postoperatively, and in one study was +19.94 D and in a second study was + 10D hyperopic . Images close to the eye should thus be blurry and appear magnified.…”
Section: Discussionmentioning
confidence: 99%
“…Intraocular lenses (IOL) could improve postoperative visual outcome. An intraocular lens with a refractive power of 25 D resulted in −3.48D myopia at retinoscopy in one study of pseudophakic horses . A second study with a 14D IOL found the postoperative retinoscopy to be closer to emmetropia at +0.4D …”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the corneal incision was enlarged to 5 mm, and either a +14D, +18D, or +25D equine‐specific foldable IOL (Acrivet‐Veterinary Division) was inserted through the incision and into the lens capsular bag using lens‐folding forceps (Acrivet‐Veterinary Division). Choice of IOL diopter power was made based on the best available information at the time of surgery in an attempt to achieve emmetropia after surgery . The hyperopic postoperative refractive status of four horses receiving the 25D diopter IOL resulted in a subsequent shift to use of the +18D IOL in adult horses .…”
Section: Methodsmentioning
confidence: 99%
“…Data collected from records included age at the time of surgery, gender, breed, surgical eye(s), etiology of the cataract, presence or absence of chronic uveitis, IOL implantation status, postoperative complications, and visual outcome at last follow‐up. Many horses had been refracted, but as evaluation of streak retinoscopy has been reported elsewhere, this information was not collected for the purpose of this study . Etiology of the cataract was surmised based on history and clinical evaluation.…”
Section: Methodsmentioning
confidence: 99%